Effectiveness of The Application of Administrative Criminal Sanctions Against Illegal Parking in The Malioboro Area - Fatmasari, Fatmasari; Retno Mumpuni, Niken Wahyuning (Universitas Tidar, 2023)
Illegal parking violations in the Malioboro area of Yogyakarta City are still rampant, causing traffic congestion and disruption. This study aims to determine how law enforcement against illegal parking and analyze the effectiveness of the application of administrative criminal sanctions against illegal parking in Malioboro area of Yogyakarta City. The normative-empirical research method is used by utilizing observation, interview, and literature study to get a comprehensive picture of the situation in the field. The results of the study identified that law enforcement against illegal parking in the Malioboro area uses two law enforcement efforts, namely preventive and repressive law enforcement efforts, in the form of conducting coaching, routine patrols, verbal reprimands, statements not to repeat, and providing administrative criminal sanctions in the form of fines. In addition, the research identified three factors inhibiting the effectiveness of the application of administrative criminal sanctions, namely law enforcement factors, society, and infrastructure. The lack of adequate parking lots, low public awareness, the imposition of fines that are not commensurate with the income of illegal parking attendants, and the high number of illegal parking attendants are the main causes of these violations.